Islamic Social Reporting Index as a Model for Measuring the Social Performance of Islamic Banking - Saputra, Ade; Putra, Purnama (Research of Islamic Economics, 2025)
This study analyzes and compares the social performance of Islamic banking in Indonesia using the Islamic Social Reporting (ISR) Index. The ISR Index assesses the extent to which Islamic banks disclose social responsibilities in line with Islamic principles. This research focuses on two Islamic business units BTN Syariah and CIMB Niaga Syariah through content analysis of their annual and sustainability reports. Using a descriptive-comparative approach and secondary data, the study evaluates ISR dimensions such as environmental responsibility, social responsibility, Sharia compliance, and other relevant aspects. The findings reveal a difference in transparency between the two banks. CIMB Niaga Syariah scored higher in several ISR dimensions, indicating a stronger commitment to Sharia-compliant social reporting. Nonetheless, both banks show positive development in improving their social disclosure. These results have significant implications for Islamic banking practitioners and regulators, encouraging greater transparency, accountability, and the formulation of effective social reporting strategies aligned with Sharia values. Furthermore, the study serves as a useful reference for other Islamic financial institutions aiming to enhance their social performance and better meet stakeholder expectations through more comprehensive and responsive reporting practices.